Exploring pharmacovigilance awareness and attitudes among healthcare practitioners in Iraq: insights from a survey-based study - Abdulmohsin Dabis, Hussein; Talib Hameed, Ali (Universitas Airlangga, 2025)
Introduction: Healthcare professionals' (HCPs) play a vital role in recognizing potential medication risks, which can lead to early interventions and positive patient outcomes. This study aims to evaluate the knowledge and attitudes of healthcare professionals regarding pharmacovigilance in Iraq. Methods: This is a cross-sectional conducted from June 13, 2023, to February 18, 2024, involving 415 healthcare providers (137 physician, 103 pharmacists, and 175 nurses) selected through convenience sampling from three public hospitals. Data collection was done through an adapted questionnaire, and the data were analyzed using descriptive statistical techniques, and Chi-square/Fisher's exact tests. P-value ≤ 0.05 was determined as significant. Results: The results showed while most participants correctly identified the purpose of pharmacovigilance (71.3%) with significant difference between groups (p=0.02), only about half (52.5%) correctly defined pharmacovigilance (p=0.21). Almost all participants (94.5%) agreed that reporting adverse drug reactions is necessary. However, there was inconsistency between this belief and actual experience, as only 18.8% reported having encountered an adverse drug reaction. Top 3 factors discouraging healthcare professionals from reporting adverse drug reactions included lack of knowledge, fear of litigation, and prolonged or complex administrative procedures. Conclusions: There were significant knowledge and attitude gaps among healthcare professionals in various aspects of pharmacovigilance. This highlights the importance of addressing these knowledge gaps and barriers to improve pharmacovigilance practices in Iraq. Targeted training programs, simplified reporting procedures, and a culture of safety regarding medications should be prioritized to enhance the reporting of adverse drug reactions.